Medication Management System: An Approach to Reduce Medication Error In Apollo Hospitals Dhaka - Mahmud, A; Noor, F; Nasrullah, M (Pulse, 2014)
Apollo Hospitals Dhaka surely stepped ahead than any other hospital of Bangladesh for reducing medication errors significantly. From the very beginning of its establishment, reducing medication errors was taken as a major challenge and effective and approved strategies were developed when no other hospital took efforts in this regard. Strategies included tracking incidents of medication errors, analyzing, reporting & arranging proper training sessions for hospital staffs etc. All four types of errors like Prescription errors, Transcription errors, Dispensing errors and Administration errors are rectified and officially reported by hospital pharmacists. Along with these, Prescription Reviewing, Medication Reconciliation, incidents of Adverse Drug Reactions (ADR) are also monitored to ensure rational drug use for patients. With all its efforts, Apollo Hospitals Dhaka was able to reduce the rate of medication errors within the internationally acceptable range. DOI: http://dx.doi.org/10.3329/pulse.v5i2.20265 Pulse Vol.5 July 2011 p.41-47